New insights into contrast-associated acute kidney injury: the key role of endothelial dysfunction - Fakhfakh, Mohamed; Lassoued, Taha; Nouri, Firas; Ibn El Mechri, Nizar; Daly, Ala; Abdessalem, Salem; Ferjani, Souad; Milouchi, Sami (Frontiers in Nephrology, 2026)
BackgroundContrast-Associated Acute Kidney Injury (CA-AKI) is a major cause of acute kidney injury in hospitalized patients, which is triggered by the administration of iodinated contrast agents during computed tomography scans and angiographic procedures. It significantly elevates cardiovascular risk and stands as a major complication of coronary angiography, contributing to a marked deterioration in patient prognosis with elevated rates of morbidity and mortality.AimOur main goal was to assess the predictive factors of CA-AKI and investigate a possible association between pre-existing endothelial dysfunction and the occurrence of CA-AKI following Percutaneous Coronary Interventions (PCI). We also intended to explore possible preventive measures of CA-AKI.MethodsWe conducted a prospective observational longitudinal study enrolling patients with an indication for PCI. Patients underwent an assessment of renal function (baseline creatinine, 24h and 48-72h after administration of contrast agent). We also evaluated renal function at one month as a secondary endpoint. Then, we analyzed Endothelial Quality Index (EQI) by Finger Thermal Monitoring (FTM) with E4 diagnosis Polymath.ResultsWe enrolled 187 patients (134 males, 53 females) in our study with a mean age of 61.1± 11.8 years. Over half (56.7%) were type 2 diabetes. A total of 60 cases of CA-AKI were reported (33.7%). The mean EQI was 0.86 ± 0.61. The vast majority of our study population (n=178; 95.2%) had endothelial dysfunction (EQI<2), and a significant proportion (n=142; 75.9%) had severe endothelial dysfunction (EQI<1). In our study, CA-AKI incidence was significantly associated with severe endothelial dysfunction (p=0.007). It was also strongly correlated to the rescue PCI (p=0.002), contrast media volume>100ml (p=0.015) and the presence of a two-vessel coronary artery disease (p=0.008). In multivariate analysis, severe endothelial dysfunction (OR = 5.46; p = 0.014), rescue PCI (OR = 5.77; p = 0.04) and contrast medica volume equal or over 140 ml (OR = 6.96; p = 0.036) were independent risk factors of CA-AKI. We found that pre- and post-hydration with isotonic saline solution and that patients whose baseline treatment includes statins, were significantly prevented from developing CA-AKI. (p=0.007 and 0.008 respectively).ConclusionOur study showed a significant association between the presence of severe endothelial dysfunction, assessed non-invasively by FTM, and the risk of developing CA-AKI. These results appear to be relevant considering that EQI is a low-cost, non-invasive and easily reproducible marker of endothelial dysfunction.